Serum-mediated inhibition of polymorphonuclear leukocyte function following burn injury. - Bjornson, A B (1981)
Serial serum samples from 12 bacteremic burned patients were tested at a physiologic concentration for their ability to facilitate phagocytosis and intracellular killing of the homologous infecting Staphylococcus aureus strains by normal human polymorphonuclear leukocytes in comparison to pooled normal human serum. Serum-mediated inhibition of leukocyte bactericidal activity was demonstrated in three of the patients during 13 to 56 days after burn. Decreased bacterial activity was related to an inhibitory effect of the burn sera on the phagocytic process, which reduced the number of internalized bacteria available for intracellular killing. The serum-mediated inhibition of phagocytosis was not found to be dependent on bacterial surface properties unique to S. aureus. The inhibitory effect was shown to involve a direct interaction of the burn sera with the leukocytes, which was not associated with cell death and was not reversed by washing of the leukocytes.